The Occurrence and Evaluation of Risk Factors Associated with Cataract in People of Pakistan: A Clinical Study - Yasir Nawaz; Saba Munir; Ambar Ayoub; Alia Iqbal; Fouzia Tanvir; Muhammad Luqman (Wolters Kluwer Medknow Publications, 2024)
Background: A cataract is the clouding of the lens in the eyes, and it is a major cause of blindness worldwide, especially in tropical regions where a significant portion of the population resides in developing nations. Purpose: This study, conducted as a population-based study at Ali Trust Eye Hospital in Okara, aimed to assess the relationship between cataracts and other risk factors in patients. Methods: A total of 1999 patients were included in the study, and clinical information such as sex, age, and education level was collected. In addition, each patient's medical history, including diabetes mellitus, blood pressure, and family history of cataracts, was documented. Results: Of the patients, 46% were male, and 54% were female. Cataracts affected individuals in various age groups, with significant differences observed (P < 0.05). The educational status of males and females did not differ significantly (P > 0.05). Notably, there was a significant difference in the prevalence of diabetes mellitus among the patients (P < 0.05), indicating reliable distinctions, whereas the prevalence of high blood pressure did not show a significant difference (P > 0.05). Family history of cataracts among patients also did not exhibit significant differences (P > 0.05). Conclusion: In conclusion, cataracts are associated with various risk factors in the human population. Age and the presence of diabetes mellitus are highly correlated with cataracts, which is a matter of primary concern. Early detection and treatment can make a significant difference in managing this condition.